Evaluation of the Effectiveness of Risk Management in Addressing Patient Safety Incidents - Aritonang, Barita (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Patient safety incidents are a serious issue affecting healthcare quality and public trust in hospitals. Effective risk management implementation is crucial to reduce adverse events. Objective: This study aimed to evaluate the effectiveness of risk management in mitigating patient safety incidents at Granmed Hospital, Lubuk Pakam. Methods: The study was conducted from September 2023 to February 2024 using a descriptive quantitative and qualitative approach. Data were collected from 50 healthcare worker respondents via questionnaires, incident report reviews, and in-depth interviews. Results: Findings showed that 78% of respondents believed risk management systems were well implemented, especially in risk identification and analysis stages. However, incident reporting was still low (43%), due to fear of punishment and lack of training. Document analysis revealed a 27% decrease in reported incidents compared to the previous year. Conclusion: Risk management at Granmed Hospital is relatively effective in reducing patient safety incidents. Nevertheless, there is a need to improve the safety culture and develop a more transparent reporting system.